The Development of Android Application Familiarization to Variety of Profession Based on Applied Science Cluster - Noor, Khilda Wulidatin; Hidayat, Dede Rahmat; Hanim, Wirda (Universitas Malikussaleh, 2019)
The purpose of this study is to develop a familiarization to the variety of professions that can be familiarized by classifying professions based on applied science clusters in Indonesia in accordance with the Constitution of the Republic of Indonesia Number 12 of 2012 concerning Higher Education in article 10 section 2 which reads: